A Review of the Structure–Activity Relationship of Natural and Synthetic Antimetastatic Compounds - Su Ki Liew; Sharan Malagobadan; Norhafiza M. Arshad; Noor Hasima Nagoor (Biomolecules, 2020)
There are innumerable anticancer compounds derived from either natural or synthetic origins. Many of these compounds have been further developed through structural modifications to not only inhibit cancer cell growth but also to exert an antimetastatic effect. This is achieved by attaching different substituents to generate different structure−activity relationships. This review highlights the effectiveness of different functional groups known to have antimigration and antiproliferation activities, such as fluoro, methoxy, methyl, amino, hydroxy, nitro, bromo, chloro, methylamino, ethoxy, carbonyl, iodo, and trifluoromethyl groups. Additionally, the positioning of these functional groups plays an important role in their anticancer activities, which was evident in one of our studies comparing analogues of a natural compound. Thus, this review suggests future recommendations for the design and development of improved anticancer drugs with higher efficacy.